VARIASI GENETIK PRODUKSI GETAH UJI KETURUNAN Pinus merkusii Jungh. et de Vriese DI KPH BANYUMAS BARAT - , IMAM MUSLIMIN; , Prof. Dr. Ir. H. Moh. Naâiem, M.Agr, Sc., ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The research aimed to assess genetic variations, estimated heritability and genetic gain in resin yield as well genetic and phenotypic correlations between resin yield and growth of P. merkusii. The study was conducted on half-sib progeny test of 4-year-old P. merkusii plantation at compartment 37C RPH Lumbir BPKH Samudra KPH Banyumas Barat, using incompletely-block-row-column design by sub-line system (sub-line SSO Jember, Sulawesi 1, SSO Sumedang, Sulawesi 2 and Jatim 2). Variables measured were diameter, height and average of resin yield from two drillings on the right and left trunk using 10 mm drill bit at 50 cm height from the ground. Genetic variation for resin yield between family was significant different except for sub-line SSO Jember. Estimated component variances family were 8.92%